Development and Application of an Interdisciplinary Rapid Message Testing Model for COVID-19 in North Carolina. (July 2021) - Bartels, Sophia M.; Gora Combs, Katherine; Lazard, Allison J.; Shelus, Victoria; Davis, C. Hunter; Rothschild, Allison; Drewry, Maura; Carpenter, Kathryn; Newman, Emily; Goldblatt, Allison; Dasgupta, Nabarun; Hill, Lauren M.; et al.
Introduction: From the onset of the COVID-19 pandemic, public health officials have sought to develop evidence-based messages to reduce COVID-19 transmission by communicating key information to media outlets and the public. We describe the development of an interdisciplinary rapid message testing model to quickly create, test, and share messages with public health officials for use in health campaigns and policy briefings. Methods: An interdisciplinary research team from the University of North Carolina at Chapel Hill assembled in March 2020 to assist the state health department in developing evidence-based messages to influence social distancing behaviors in the state. We developed and iteratively executed a rapid message testing model; the components of the 4-step model were message creation, survey development, survey administration, and analysis and presentation to health department officials. The model was executed 4 times, each during a 7-day period in April and May, and each subsequent survey included new phrasing and/or messaging informed by the previous week's survey. A total of 917 adults from North Carolina participated in the 4 surveys. Results: Survey participants rated messages focused on protecting oneself and others higher than messages focused on norms and fear-based approaches. Pairing behaviors with motivations increased participants' desire to social distance across all themes and subgroups. For example, adding "Protect your grandmother, your neighbor with cancer, and your best friend with asthma, " to messaging received a 0.9-point higher score than the base message, "Stay 6 feet apart from others when out in public." Practice Implications: Our model to promote social distancing in North Carolina during the COVID-19 pandemic can be used for rapid, iterative message testing during public health emergencies.